The Relationship Between Human Capital and Digital Literacy on Financial Inclusion - Nur, Muh.; Karim, Kurniati; Alfiana, Alfiana; Windreis, Christ; Renggaala, Nuniek Yuniarti Ningsih (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Financial inclusion is a crucial element in promoting sustainable and equitable economic development. However, the level of financial inclusion still faces various challenges, particularly those related to the quality of human resources and the ability to adapt to digital technology developments. This study aims to analyze the relationship between human capital and digital literacy on financial inclusion. This study used a qualitative approach with a descriptive-exploratory design. Data were collected through in-depth interviews, observations, and documentation with productive-age individuals, micro and small business owners, and related parties involved in formal financial services. Data analysis was conducted using thematic analysis to identify patterns and meanings emerging from the experiences and perceptions of informants. The results show that human capital plays a significant role in shaping individuals' understanding, attitudes, and trust in formal financial services. Education level, skills, and experience contribute to an individual's ability to access and utilize financial services. Furthermore, digital literacy has proven to be a crucial factor in supporting the utilization of technology-based financial services, particularly in increasing access, security, and intensity of use of digital financial services. This study also found that human capital and digital literacy have a mutually reinforcing relationship in promoting financial inclusion. Individuals with high levels of human capital and digital literacy demonstrate higher and more sustainable levels of financial participation. These findings emphasize that increasing financial inclusion must be accompanied by strengthening the quality of human resources and digital literacy within the community.